9x*-12x+4=0

Simple and best practice solution for 9x*-12x+4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x*-12x+4=0 equation:


Simplifying
9x * -12x + 4 = 0

Reorder the terms for easier multiplication:
9 * -12x * x + 4 = 0

Multiply 9 * -12
-108x * x + 4 = 0

Multiply x * x
-108x2 + 4 = 0

Reorder the terms:
4 + -108x2 = 0

Solving
4 + -108x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -108x2 = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -108x2 = 0 + -4
-108x2 = 0 + -4

Combine like terms: 0 + -4 = -4
-108x2 = -4

Divide each side by '-108'.
x2 = 0.03703703704

Simplifying
x2 = 0.03703703704

Take the square root of each side:
x = {-0.19245009, 0.19245009}

See similar equations:

| -1(x-6)=8x-12 | | 8p-28=-22+9p | | 1000000+1=x | | 32x+8y=5600 | | 5(2m-5)=7-(m+3) | | -5a+6a=-10+3a | | 432=x(x-6)(x-6) | | -5p+8+6p=10 | | x+3x=4x | | .5x-1.5=-6.5 | | (180x-1800)/(x)(x-20) | | 3x-45-3x= | | x=5/8y | | Y^2+9=6y | | 38=0.4n | | 3n+2+1=-21 | | 7+(4+4)= | | 0.3x=26 | | x1/10 | | 11=x-5+8 | | 3n+2+1=-2 | | x(x-6)(x-2)=996 | | 49w=-8 | | 8(x-2)=2x+8 | | 15t-14=-14 | | 9=-5r-4r | | -1(x-6)= | | 8x^2+2x+9=0 | | -9(6n+4)=18-5n | | 2(6x+6)= | | 2=4k-5k | | 8a+24=-16 |

Equations solver categories